Memory-based Immune Network for Multi-Robot Cooperation - Razali, Sazalinsyah; Meng, Qinggang; Yang, Shuang-Hua (2009)
In this paper, basic biological immune systems and their responses to external elements to maintain an organism's health state are fully described. The relationship between immune systems and multi-robot systems are also discussed. Our proposed algorithm is based on immune network theories that have many similarities with the multi-robot systems domain. The paper describes a memory-based immune network that enhance a robot's action-selection process and can obtain an overall a quick group response. The algorithm which is named as Immune Network T-cell-regulated|with Memory (INT-M) is applied to the dog and sheep scenario. Simulation experiments are being conducting on the Player/Stage platform and experimental data are being evaluated.